Coronary microvascular dysfunction in autoimmune rheumatic diseases: beyond coronary flow velocity reserve - Cecere, Annagrazia; Perazzolo Marra, Martina; Zanatta, Elisabetta; Civieri, Giovanni; Iliceto, Sabino; Tona, Francesco (Frontiers in Cardiovascular Medicine, 2024)
Autoimmune rheumatic diseases (ARDs) are a heterogeneous group of disorders characterized by an inappropriate immune reactivity against different body tissues. Patients affected by ARDs present increased cardiovascular morbidity and mortality, which significantly impacts long-term prognosis. Endothelial dysfunction, inflammation, oxidative stress, and autoimmunity are strictly involved in atherosclerosis progression and coronary microvascular dysfunction (CMD), both of which contribute to increased cardiovascular risk. CMD represents the inability of the coronary microvasculature to respond with vasodilation to increased cardiac metabolic demands and can be assessed by non-invasive and invasive imaging tests. Coronary flow velocity reserve assessed by echocardiography has been demonstrated to accurately identify ARDs patients with CMD. However, stress cardiac magnetic resonance (CMR) accurately assesses myocardial ischemia, perfusion, and viability in ARDs patients. The myocardial perfusion reserve index (MPRI) is a robust semiquantitative imaging marker that represents the vasodilatory capacity of the coronary microcirculation in response to a vasodilator stress. In the absence of significant coronary stenosis, ARDs patients revealed a reduced MPRI in comparison with the general population, regardless of the presence of myocardial fibrosis. Identification of CMD in asymptomatic patients could be crucial to precociously start targeted medical therapy, avoiding major adverse cardiac events in this clinical setting. This review aims to summarize the current evidence regarding CMD in ARDs patients, focusing on the role of stress CMR and the promising myocardial perfusion analysis.